حجية إجماع أهل المدينة وأثره في توجيه الخلاف بين الفقهاء عند ابن رشد الحفيد: دراسة أصولية فقهية تطبيقية على كتاب الصلاة - الخلايلة، أنس محمد عوض (الجامعة الإسلامية بالمدينة المنورة, 2021)
يعد إجماع أهل المدينة من الأدلة المختلف في حجيتها عند الفقهاء، ومن الأدلة المعتبرة عند المالكية، تأتي هذه الدراسة لعرض هذا الأصل عند الإمام مالك والنظر في تأصيله وتأثيره في الفروع وفق ما سار عليه ابن رشد الحفيد في كتابه "بداية المجتهد"، وإبراز أهمية إجماع أهل المدينة كدليل معتبر عند بعض الفقهاء، مع الأخذ بعين الاعتبار أن الإمام مالك لم يكن يميل إلى التوسع في إعمال هذا الأصل ولا الأخذ به ولا سيما في مقابلة خبر الآحاد الذي ثبتت صحته. ولهذا كان لابد من بيان المواطن التي يقوى به أثر عمل أهل المدينة في التأثير على غلبة الظن بثبوت الخبر أو عدم ثبوته حتى لا يأتي بعد ذلك من يسيء فهم منهج الإمام مالك -رحمه الله تعالى- فيما ذهب إليه من ضوابط يحكم بها على الأخبار من حيث القبول والرد. إن أقوال الإمام مالك تؤيد رد خبر الواحد إذا ما عارضه عمل أهل المدينة لاعتبارات معينة، ولذلك نجد آثاراً واضحة مترتبة على الخلاف حول حجية هذا الدليل بين الجمهور والمالكية، ما يعني أن للمسالة ثمرة جلية في الفروع الفقهية؛ وبناءً على ذلك فإن هذه المسألة ليست من تلك المسائل الأصولية قليلة النيل فقهياً بل هي مسألة حية وعملية.
The consensus of the people of Madinah is regarded one of the proofs that were disputed among the jurists regarding their authority, and its authority is approved in the Maliki School. This study aims to highlight this proof according to Imam Malik and to examine its authority and influence on the Furu‘ (the off-shoot rulings of jurisprudence) according to the approach of Ibn Rushd the grandson in his book “Bidayat al-Mujtahid”, and highlighting the importance of the consensus of the people of Madinah as a significant proof for some jurists, taking into account that Imam Malik was not inclined to an extensive application or adoption of this proof especially in interface with Khabar Al-Ahad (the hadith of singular reporters) that has been proven to be authentic. Hence, it is necessary to clarify the issues by which the effect of the custom of the people of Madinah is strengthened in influencing the prevalence of thinking that the Hadith has been proven to be authentic or not, so that no one will henceforth misconstrue Imam Malik’s approach - may Allaah Almighty have mercy on him - pertaining to the conditions he used to rule with on Hadiths regarding their acceptance or their rejection. The sayings of Imam Malik support the rejection of Khabar Al-Ahad if it is opposed by the custom of the people of Madinah for specific considerations, and therefore we find clear implications resulting from the disagreement about the authenticity of this proof between the majority and the Malikis, which means that the issue has a clear impact in the off-shoot issues of jurisprudence. Hence, this issue is not one of the Usuli (fundamentalist) issues with few Fiqh (jurisprudential) impacts; rather it is a lively and empirical issue.
Keywords: أصول الفقه الإسلامي -- الاختلاف الفقهي -- العبادات الإسلامية -- أحكام الصلاة -- ابن رشد، محمد بن أحمد بن محمد، ت. 595 هـ